2009
DOI: 10.1002/bem.20537
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of germination and early growth of wheat and bean seedlings grown under various magnetic field and osmotic conditions

Abstract: Magnetic field (MF) can have different effects on plant metabolism depending on its application style, intensity, and environmental conditions. This study reports the effects of different intensities of static MF (4 or 7 mT) on seed germination and seedling growth of bean or wheat seeds in different media having 0, 2, 6, and 10 atmosphere (atm) osmotic pressure prepared with sucrose or salt. The germination percentages of the treated seeds were compared with untreated seeds germinated in different osmotic pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 28 publications
3
47
0
5
Order By: Relevance
“…Scientists have found an induction of primary root curvature in radish seedlings in a static magnetic field, roots responded tropically to magnetic field with the tropism appearing to be negative; these roots responded significantly to the south pole of the magnet (Yano, et al 2001). The application of magnetic field doses of 4 mT and 7 mT promoted germination ratios of bean and wheat seeds (Cakmak, et al 2010). Magnetic treated pea plants grew higher and heavier than control; the greatest differences were observed for seeds treated with doses of 125 mT and 250 mT, for 24 hours or permanent.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have found an induction of primary root curvature in radish seedlings in a static magnetic field, roots responded tropically to magnetic field with the tropism appearing to be negative; these roots responded significantly to the south pole of the magnet (Yano, et al 2001). The application of magnetic field doses of 4 mT and 7 mT promoted germination ratios of bean and wheat seeds (Cakmak, et al 2010). Magnetic treated pea plants grew higher and heavier than control; the greatest differences were observed for seeds treated with doses of 125 mT and 250 mT, for 24 hours or permanent.…”
Section: Introductionmentioning
confidence: 99%
“…It has shown that magnetic and electromagnetic treatments enhance the salinealkali tolerance (Xi et al, 1994), enhance seed germination and seedling growth under heat stress (Ružič and Jerman, 2002;Cakmak et al, 2010), and improve plant osmotic tolerance (Karimi et al, 2012). In contrast, Yao et al (2005) showed that MF treatments enhanced sensitivity of cucumber seedlings to UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Application of magnetic fields of extremely low frequencies positively affects seed germination, shoot development, plant length, fresh weight, fruit production and mean fruit weight (Cakmak et al, 2010). The positive effects of magnetic fields have also been shown in the biosynthesis of proteins, cell production, photochemical activity, respiration rate, enzyme activity and nucleic acid content (Stange et al, 2002).…”
Section: Magnetic Field Energymentioning
confidence: 99%